Priority Factors of Innovation for the Development of Country - Zakharov, Dmytro; Ciobanu , Ghenadie (Public Policy and Accounting, 2022)
The article analyzes the impact of education, investment climate, and ease of doing business in the country on its innovative development. The correlation is set at 0.67. The influence of each of the factors on the level of economic development is analyzed. The greatest interdependence was found between the level of education and the level of innovative development. The analysis shows that the selected factors are critical for the development of innovation in the country and need attention from both the state and the business environment. Improving the quality of education promotes innovation and thus stimulates economic growth. At the same time, economic growth is the basis and important condition for the development of education, including technical. The innovative business environment is sensitive to the complexity of regulations. In addition to incentives, the state must provide accessible and transparent rules for innovative business. Investing in innovation is a crucial factor in transforming the economic system. Innovation and investment are interconnected and cannot exist in isolation. The growing share of both government and business investment in research and development contributes to exponential growth.